Effect of integrated nutrient management on wheat (Triticum aestivum) yield, nutrient uptake and soil fertility status in alluvial soil - SINGH, S P (The Indian Journal of Agricultural Sciences, 2019)
A field experiment was conducted on alluvial soil at SVP University of Agriculture and Technology Meerut (UP) during winter (rabi) season of 2013-14 and 2014-15 to study the effect of integrated nutrient management (INM) on yield, nutrient uptake of wheat (Triticum aestivum L.) and soil fertility. The experiment was laid-out in a randomized complete block design with 9 treatments and 3 replicates. The results revealed that plant height, tillers/m, spike length, grains/spike test weight, and grain and straw yields increased significantly over control due to fertilizer application. The grain (5 t/ha) and straw (6.88 t/ha) yields at 100% NPK were 79.7 and 78.2% higher than the control. The yield of wheat was improved further with conjoint application of 75% NPK + organic manures (OM). The maximum values of growth, yield attributes and grain (5.39 t/ha) and straw yield (7.33 t /ha) were recorded with 75% NPK + 5 t FYM + 2.5 t VC/ha closely followed by 75% NPK + 2.5 t VC + 3.75 t press mud (PM)/ha. Application of VC and FYM was found to be more beneficial in terms of growth and yield of wheat. The uptake of N, P, K, S, and Zn by wheat crop was highest at 75% NPK + 5 t FYM + 2.5 t VC/ha and lowest in control. The use of organic manures decreased soil pH and their combined use with fertilizers was significantly reflected in the buildup of organic C, available N, P, K, S and DTPA-extractable Zn content of the post-harvest soils. The minimum amount of available nutrients in post-harvest soil was recorded under control.